PENGUATAN NILAI PEDULI SOSIAL MELALUI PROGRAM BAKTI SOSIAL BERBASIS PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Uswatul Hasanah; Khusnan Iskandar; Fitriana Nur Hidayah (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
The rapid advancement of digital technology has influenced students’ social behavior, particularly in terms of social interaction and concern for others. This condition presents a challenge for educational institutions in fostering students’ social character. Therefore, social service programs based on Islamic Religious Education (PAI) are considered an effective medium for strengthening social care values among students. This study was conducted at SMP Assa'adah Surabaya with the aim of exploring the implementation of social service programs in strengthening students' social care values, identifying the values developed through these activities, and examining the factors that support and hinder their implementation. This study employed a qualitative approach using a descriptive case study design. Data were gathered through observations, interviews, and documentation involving the principal, Islamic Religious Education teachers, student affairs personnel, and students participating in social service activities. The collected data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that social service activities at SMP Assa'adah Surabaya are implemented through various programs, including Friday charity collections, fundraising initiatives, social aid distribution, and environmental service activities. These programs contribute significantly to the development of social care values such as empathy, solidarity, cooperation, mutual assistance, and social responsibility. Furthermore, students demonstrated positive behavioral changes through increased participation in social activities and greater awareness of community needs. The successful implementation of these programs is supported by school commitment, teacher involvement, and a conducive religious environment. However, challenges remain, including limited time allocation, differences in students’ levels of social awareness, and the influence of digital media on students’ social engagement. The study concludes that social service programs integrated with Islamic Religious Education can serve as an effective strategy for strengthening students’ social character in the digital era.